Analisis Stilistika Pada Puisi “Maqomat Cinta” Karya Heri Isnaini - Aini Ulwi Sifa (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The study is intended to identify the use of figures of speech (majas), describing the words of heri isnaini's